Working toward transformation: educational leaders' use of continuous improvement to advance equity - Stosich, Elizabeth Leisy (Frontiers in Education, 2024)
I conducted a comparative case study of three networked improvement communities (NICs) situated in the same school district to understand how educational leaders applied continuous improvement (CI) structures, practices, and tools to address equity-focused problems of practice. The district that is the focus of this study represents a critical case for understanding educational leaders’ use of CI approaches as a lever for equity-focused school reform because the district and state in which it was situated had made ongoing investments in both advancing equity in schools and using various CI approaches. Data collection and analysis focused on interviews with four district leaders and eight school leaders, observations of approximately 24 hours of NIC meetings and planning meetings, and document collection. I draw on sensemaking theory to understand the factors that supported and/or constrained the use of CI to advance equity. Further, the study draws on Gutiérrez’s (2012) framework for equity to understand the range of equity work in which they engage as they identify problems and design solutions as part of CI, including more dominant and transformative dimensions of equity. The district's sustained investments in equity-focused reform fostered beliefs, mindsets, and leadership capacity among school and district leaders that supported them in working towards equity-focused goals in each NIC. Study findings suggest that the focus on cycles of inquiry supported leaders in taking action to advance equity, and attention to student voice encouraged more transformative equity work.